An ESIPT-based fluorescent probe with large Stokes shift for peroxynitrite detection in HeLa cells and zebrafish. (August 2022) - Yu, Jin; Shu, Wei; Kang, Hao; Han, Rubing; Zhang, Xiaoli; Zhang, Rubo; Jing, Jing; Zhang, Xiaoling
Abstract: The quick coupled reaction of nitric oxide (NO) with superoxide free radicals (·O2 − ) produces peroxynitrite (ONOO − ), it is a powerful biological oxidant. And according to interact with proteins, lipids, nucleic acids and other organisms, the ONOO − eventually leads to all sorts of diseases, for instance, Alzheimer's disease, diabetes, cancer, inflammation. To fully understand the multiple pathological processes of ONOO − in vivo, it is imperative to exploit effective tools to realize the precise, fast and sensitive detection of endogenous ONOO − . We described a novel fluorescent probe named YV in this work, covering the synthesis, characterization and biological application. YV can detect ONOO − by means of fluorescence imaging. Because of the borate group cleavage, YV exhibited a fluorescence intensity change toward ONOO − . It was, the principle of ESIPT that resulted in fluorescence enhancement. The probe YV shows a series of advantages such as high selectivity, fast response, significant Stokes shift and low detection limit. Fluorescence imaging can be used to identify variations in ONOO − in Hela cells and zebrafish. YV will be a robust imaging tool for detecting endogenous ONOO − . Graphical abstract: ESIPT mechanism-based fluorescent probe with large Stokes shift for detection of peroxynitrite in HeLa cells and zebrafish was successfully developed. Image 1 Highlights: YV has a large stokes shift, low background interference, and high detection sensitivity (LOD = 17.3 nM). YV displayed high specificity toward ONOO − over other reactive oxygen species with a fast response. YV was successfully applied for monitoring the fluctuation of ONOO − in Hela cells and zebrafish.